Use Multiplex PCR For Detection of Some Virulence Genes of Klebsiella Isolated From Different Environmental loci - Zena J. Mohammed; Ali H. Abdulkareem; Ahmed A. Sulaiman (مجلة جامعة الانبار للعلوم الصرفة, 2015)
This study includes collected of 399 samples from different sources included clinical and non clinical samples. 293 clinical samples (urine, wounds, burns, stool, sputum). Non- clinical samples included 106 samples (water, soil) from November 2014 through February 2015. 51 samples were diagnosed as K. pneumoniae using phenotypic, biochemical and cultural diagnosis features and definitely diagnosed with API20E and vaitek test. Results of antibiotic resistance against different antibiotics showed that K. pneumoniae isolated from clinical and non- clinical samples varied in their resistance to these antibiotics and all isolates were sensitive 100% to Imipenem. A number of specific primers were designed to detect bacteria by using distinct gene and also to detects resistance to antibiotics using multiplex PCR technology for the presence or absence of 8 genes(magA, rmpA, htrA, Uge-1, gent-2,blaCTX, terA-1,StrA-2) that encodes for main virulence factors to diagnose K. pneumoniae. The result showed that that 45 isolates had rmpA which might be used as detection marker, in the same reaction of multiplex PCR detection of 4 genes related with resistance to different antibiotic groups(StrA,terA,blaCTX,gent-2) were done all K,pneumoniae contained StrA gene. According to this study we can concluded that multiplex PCR can use to distinguish isolated bacteria from different sources more correctly and also to determine its antibiotic resistance that are widely used in short time and little effort without need to routine testing.